Current Status and Future of Multidisciplinary Team in Hepatocellular Carcinoma - Jinbin CHEN; Yaojun ZHANG; Minshan CHEN (Zhongliu Fangzhi Yanjiu, 2025)
Hepatocellular carcinoma (HCC) poses a significant hazard to public health in China because of its high incidence, high mortality, and high rate of advanced stages. Early detection and treatment of HCC by screening for high-risk populations is instrumental for enhancing survival rates among patients with HCC in China. Liver resection, local ablation, interventional therapy, radiotherapy, and drug therapy are all effective treatments for patients with HCC, and appropriate treatments can be selected based on different tumor stages. However, the condition of patients with HCC in China is complicated, and no single specialty offers the complete spectrum of care. The disease-centered multidisciplinary team for HCC is a crucial method to prolong the survival of patients with HCC and optimize their quality of life. Recent advancements in different disciplines have brought new opportunities in HCC treatments and altered multidisciplinary management approaches. Meanwhile, new challenges have emerged, and many problems have yet to be addressed.